Sphingosine 1-phospate differentially modulates maturation and function of human Langerhans-like cells. Issue 1 (April 2016) - Bock, Stephanie; Pfalzgraff, Anja; Weindl, Günther
Highlights: Human LCs express a distinct S1P receptor profile. Activation of S1P receptors does not induce complete maturation of human LCs but reduces cytokine release in mature LCs. S1P is a chemoattractant for LCs and reduces migration of immature and mature MUTZ-LCs but not MoLCs. Exogenous and endogenous S1P signalling is dispensable for LC endocytosis. Abstract: Background: As mediators between innate and adaptive immune responses, Langerhans cells (LCs) are in the focus of recent investigations to determine their role in allergic inflammatory diseases like allergic contact dermatitis and atopic dermatitis. Sphingosine 1-phosphate (S1P) is a crucial lipid mediator in the skin and potentially interferes with LC homeostasis but also functional properties, such as cytokine release, migration and antigen-uptake which are considered to be key events in the initiation and maintenance of pathological disorders. Objective: Here, we used human Langerhans-like cells to study the influence of S1P-mediated signalling on LC maturation, cytokine release, migration and endocytosis. Methods: Immature Langerhans-like cells were generated from the human acute myeloid leukaemia cell line MUTZ-3 (MUTZ-LCs) and human primary monocytes (MoLCs). S1P receptor expression was determined by quantitative RT-PCR and western blotting. Expression of maturation markers were investigated by flow cytometry. The influence of S1P signalling on cytokine release was quantified by ELISA. Migration assays and FITC-dextran uptake in the presence of S1P, specific S1 P receptor agonists and antagonists as well as fingolimod (FTY720) were analysed through fluorescence microscopy and flow cytometry. Results: S1P receptor protein expression was confirmed for S1P1, S1P2 and S1P4 in MUTZ-LCs and S1P1 and S1P2 in MoLCs. In mature cells S1P receptors were downregulated. S1P did not induce maturation in MUTZ-LCs, whereas in MoLCs CD83 and CD86 were slightly upregulated. IL-8 release of MUTZ-LCs matured in the presence of S1P was not altered, however, reduced IL-6 and IL-12p70 levels were observed in mature MoLCs. Interestingly, immature MUTZ-LCs revealed a significantly increased S1P-dependent migratory capacity, whereas CCL20 induced migration was significantly decreased in the presence of S1P. Furthermore, migratory capacity towards CCL21 in mature MUTZ-LCs but not MoLCs was significantly lower when cells were stimulated with S1P. S1P, FTY720 and specific S1P receptor agonists did not modulate the endocytotic capacity of immature MUTZ-LCs and MoLCs. These findings were further supported by testing specific antagonists of S1P1−4 in the absence or presence of S1P. Conclusion: Our data demonstrate that S1P regulates key events of human LC maturation including cytokine release and migration. These findings are of particular importance when considering the potential use of S1P in inflammatory skin disorders.